NutriChew:a Feasibility Study on the potential market and sustainable production of chewy vegetables with dips as a nutritious snack alternative in San Nicolas, Binondo. - Eimar, Thea Jonelyn B. Esteban, Frances Carlyn B. Fuentes, Roan C. Lao, Nicolette Gail Y. Pimentel, Kyla Mae B. Reyes, Linella Joyce V. 4 0 16; 5
u
Feasibility Study : (BSBA major Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2